(untitled) (Research, Society and Development, 2025)
This study aimed to identify the prevalence of Equine Infectious Anemia (EIA) in the state of Rondônia from 2019 to 2025. The research was descriptive, based on quantitative methods, and the study universe consisted of data released by the Rondônia State Agricultural and Livestock Health Defense Agency (IDARON) regarding cases of equine infectious anemia. The sample comprised equine cases presenting with EIA. The Interactive Demonstration and Disease Investigation Tool was used, and searches were conducted in the virtual databases Google Scholar, SciELO, among others. The results showed that, during the years 2019 to 2025, 102 (100%) investigations of EIA occurred in Rondônia, of which 94 (100%) involved blood collection, with 57 (61%) positive cases and 37 (39%) negative occurrences. There was a prevalence of investigations in the year of In 2019, 72 (70.60%) investigations were carried out, and in 2021, 8 (7.84%) investigations were conducted. It is concluded that the State has maintained regularity in the control of AIE (Acute Equine Infectious Anemia), especially through the activities carried out by IDARON, as verified in the data from the last 7 years. It was observed that the number of positive cases has been decreasing consecutively; therefore, it is believed that monitoring is fundamental, and in the suspicion of new cases, tests should be carried out promptly, since early confirmation makes it plausible to reduce the risks of new contamination occurrences.